Body Composition, Aerobic Fitness, Isokinetic Profile, and Vertical Jump Ability in Elite Male and Female Volleyball and Beach Volleyball Players - Freire, Raul; Hausen, Matheus; Pereira, Glauber; Itaborahy, Alex (Journal of science in sport and exercise (Online), 2023)
Purpose This study aimed to compare the physical attributes of male and female Volleyball and Beach Volleyball athletes. Methods Fifty-five athletes from Volleyball (Male, n = 19, age 27.3 ± 6.1 years, body mass 93.2 ± 9.9 kg, and height 196.8 ± 7.4 cm and Female, n = 16, age 28.0 ± 5.6 years, body mass 76.9 ± 8.8 kg, and height 179.9 ± 5.8 cm) and Beach Volleyball (Male, n = 10, age 26.8 ± 3.4 years, body mass 92.9 ± 9.9 kg, and height 195.3 ± 7.9 cm and Female, n = 10, age 31.1 ± 6.2 years, body mass 74.6 ± 8.5 kg, and height 180.9 ± 6.0 cm) participated in the study. All tests were performed in a single visit to the laboratory in the following order: body composition, vertical jump (squat and countermovement jump), isokinetic (knees and shoulders), and cardiopulmonary exercise testing. All variables were analyzed using a two-way ANOVA (Sex and Sport factors) for independent groups. Results Beach Volleyball athletes presented lower body fat ( P = 0.03; ES = 0.32) and higher maximal cardiorespiratory variables (VO 2 , HR, and vVO 2max ). Only flexion bilateral difference (knee) at 60°/s was affected by sex ( P = 0.002; ES = 0.63). For shoulders, only dominant external/internal rotation ratio presented a significant interaction for sport and sex ( P = 0.05; ES = 0.28). Regarding vertical jumps, Volleyball male players presented a greater elastic index than BV male players ( P = 0.002, ES = 0.67). Conclusion Beach Volleyball players are thinner and have better cardiorespiratory fitness than Volleyball players. Also, they presented less use of elastic properties for vertical jumping and have a greater muscle imbalance in the hamstrings than Volleyball players.